Critical swimming speeds of wild-caught sand-smelt Atherina presbyter larvae - Faria, Ana Margarida (2014)
Swimming abilities of wild-caught sand-smelt Atherina presbyter larvae were assessed as critical swimming speed (Ucrit) throughout ontogeny. The mean Ucrit increased with size, ranging from 3⋅6 to 18⋅7 cms−1, over the size range of 6⋅6–21⋅0mm LT. This indicates that at hatching A. presbyter larvae, far from being passive floaters, are already capable of active behaviours, which may influence their dispersal patterns.